Capsular management in the arthroscopic treatment of the femoro-acetabular impingement in athletes: our experience - Di Benedetto, Paolo; Zangari, Andrea; Mancuso, Francesco; Buttironi, Michele Mario; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work In the last decade arthroscopic treatment of hip diseases has significantly spread and evolved and currently it represents the gold standard for the treatment of femoral-acetabular impingement in athletes. The function of the joint capsule has been better understood, opening a heated debate. The aim of the present retrospective study is to assess the influence of different capsulotomy techniques and a possible capsular suture role on the patient’s functional outcome in a cohort of patients with femoral-acetabular impingement arthroscopically treated. Methods 36 patients (competitive athletes) treated with hip arthroscopy for femoral-acetabular impingement have been retrospectively enrolled during a period of two years (2016-2018). Patients have been divided into three equivalent groups, 12 without a suitable capsular management (T-Capsulotomy technique), 12 performing a Longitudinal Capsulotomy but without a final suture and 12 treated with a conservative Longitudinal Capsulotomy and a capsular suture. Patient’s post-operative functional outcome has been analysed using the modified Harris Hip Score (mHHS), the Hip Outcome Score-Activity of Daily Living (HOS-ADL) and the Hip Outcome Score-Sport Scale (HOS-SS). Return to sport. Results In our series there was no statistically significant difference in functional scores, however longitudinal capsulotomy seems to be associated with a higher percentage of return to sports activity (91,6% vs 75%). Conclusions The new longitudinal shape capsulotomy technique and a capsular suture with a single side-to-side stitch at the end of the procedure in athletes can positively influence the patient’s functional outcome.